Patterns of service utilization among youth with substance use service need: a cohort study - Nikki Ow; Kirsten Marchand; Guiping Liu; Emilie Mallia; Steve Mathias; Jason Sutherland; Skye Pamela Barbic (BMC, 2023)
Abstract Background Integrated youth services (IYS) are vital to addressing the needs of youth who use substances. Evidence on the characteristics of youths accessing these services and the types of services accessed have been limited. The objectives were to identify sociodemographic, self-reported health and mental health, patterns of service utilization (service type and frequency of visits) among youths with different levels of substance use service needs (low, moderate, and high), and to estimate the extent to which substance use service needs, self-reported health and mental health influenced the frequency of visits and types of service utilized. Methods Data were collected from youth (12-24 years) accessing IYS centres in Canada. Information on socio-demographic factors, substance use in the last month, self-rated health measures, number of service visits, and type of services utilized were included. Poisson regression was used to estimate the relationship between substance use needs and number of service visits and the different type of services utilized. Results Of 6181 youths, 48.0% were categorized as low substance use service needs, 30.6% had moderate needs and 21.4% had high needs, with higher proportion of men in the high needs group. Mental health and substance use (MHSU) services were utilized the most across all three groups, followed by counseling. The median number of visits was 4 for the low and moderate needs group and 5 in the high needs group. People with high service needs had 10% higher rate of service visits and utilized 10% more services than people with low service needs (service visits: RR = 1.1 (95%CI: 1.1-1.2); service type: RR = 1.1 (95%CI:1.0-1.1)). The rate of service visits increased by 30 to 50% and the number of services increased by 10-20% for people who rated their health good/fair/poor. Similarly, the rate of service visits increased by 40 to 60% and the number of services increased by 20% for people who rated their mental health good/fair/poor. Conclusions and impacts Our study highlighted that regardless of service needs, youth who use alcohol and drugs have complex intersecting needs that present once they access integrated youth services.